2008
DOI: 10.1002/bit.22201
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the limitations on recombinant gene expression in CHO cell lines with varying luciferase production rates

Abstract: Mammalian cell lines are currently employed as one of the main cellular factories for the expression of recombinant protein-based drugs. The establishment of high-producing cell lines typically begins with a heterogeneous starter population of cells, from which the highest producing cells are selected via empirical approaches. This approach is time consuming, and is likely to encounter natural upper limits imposed by the inherent biology of the cell lines in question. In an attempt to understand both the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
(17 reference statements)
0
25
0
Order By: Relevance
“…For example, the viable cell number in the CHO52 cell line declined from day 8 to day 9 much more than the other cell lines. In terms of productivity, Null8 is a non-producing cell line that has been through the same GS selection process as the mAb-producing cell lines, but lacks the heavy and light chain IgG genes, while CHO52 was ranked as a low producer and CHO137 and CHO42 were considered high producers for the present study with their estimated specific production rates (pg/cell/h), having previously been estimated as 0.032, 0.49 and 0.31, respectively [8]. Western blot analysis for the amount of mAb in the cell culture supernatant on different days throughout culture confirmed the relative productivities of these cell lines, with CHO42 being the highest producer and CHO52 the lowest (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the viable cell number in the CHO52 cell line declined from day 8 to day 9 much more than the other cell lines. In terms of productivity, Null8 is a non-producing cell line that has been through the same GS selection process as the mAb-producing cell lines, but lacks the heavy and light chain IgG genes, while CHO52 was ranked as a low producer and CHO137 and CHO42 were considered high producers for the present study with their estimated specific production rates (pg/cell/h), having previously been estimated as 0.032, 0.49 and 0.31, respectively [8]. Western blot analysis for the amount of mAb in the cell culture supernatant on different days throughout culture confirmed the relative productivities of these cell lines, with CHO42 being the highest producer and CHO52 the lowest (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have suggested that the yield of recombinant proteins from cultured mammalian cells is in part attributed to translation efficiency [8,44]. mTORC1 exerts its influence on translation via the mTORC1 effectors 4E-BP1, p70 S6 kinase and eEF2K.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to address this issue, a number of proteomic, transcriptomic and metabolic based studies have now been undertaken and the subsequent data used to develop models to predict the phenotype of a given cell line (e.g. Clarke et al, 2011;Clarke et al, 2012;Doolan et al, 2013;Jacob et al, 2010;Mead et al, 2009;Mead et al, 2012;Meleady et al, 2011;Sanchez et al, 2014;Selvarasu et al, 2012), however these models are usually developed from cell line data at the end of the cell line development process.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address this issue, a number of proteomic, transcriptomic and metabolic based studies have now been undertaken and the subsequent data used to develop models to predict the phenotype of a given cell line (e.g. Clarke et al, 2011;Clarke et al, 2012;Doolan et al, 2013;Jacob et al, 2010;Mead et al, 2009;Mead et al, 2012;Meleady et al, 2011;Sanchez et al, 2014;Selvarasu et al, 2012), however these models are usually developed from cell line data at the end of the cell line development process.The goal of this work was to develop a screening system that would allow the selection of highly productive cell lines for monoclonal antibody (mAb) production early in the cell line development process that would use substantially less resource to achieve the same or better success rate as current methods. The vision was to be able to select a small number of cell lines based upon the analysis of data generated in multi-well plates, and take these straight to a lab-scale bioreactorevaluation stage (10 L) with a high probability that the selected cell lines were highly productive.…”
mentioning
confidence: 99%